Teaching and Local Culture Strategy on Strengthening Populous Economy - Mahmuddin, Mahmuddin (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study is to know the local culture and teaching strategies on strengthening the economy of the people in Bira village. The research question is how economic portrait of Bira village people and how is the role of local cultural and teaching strategies on strengthening the economy? The method used is qualitative research, through sociological approach, an approach that analyzes the social condition of the society as a whole among and its relation among the members in the community. Data premier source are women of Bira community, religous, local formal and informal, tourism figures, and related books as secondary data. Data are gathered through observation, interviews and document documentary analysis, data then analyzed through qualitative technique. The research shows that women are the backbone of the economy, after losing their husbands, through a weaving economic activity. There are two types of weaving apparels, namely Traditional Looms (TL) and Manual Looms (ML). The role of local culture and propagation strategies in strengthening the economy of Bira village people is sincere intention to be introduced in work, strengthen work ethic as part of Islamic teachings, teaches the importance of the honesty value and trustworthiness, instill values mandate in work and push to manufacture in woven gloves periodically as part of the local culture that needs to be preserved.